2023
DOI: 10.1186/s12934-023-02113-2
|View full text |Cite
|
Sign up to set email alerts
|

Lipid production and cellular changes in Fremyella diplosiphon exposed to nanoscale zerovalent iron nanoparticles and ampicillin

Abstract: With the dramatic decrease in fossil fuel stocks and their detrimental effects on the environment, renewable energy sources have gained imminent importance in the mitigation of emissions. As lipid-enriched energy stocks, cyanobacteria are the leading group of microorganisms contributing to the advent of a new energy era. In the present study, the impact of Nanofer 25 s nanoscale zero-valent iron nanoparticles (nZVIs) and ampicillin on lipid production and cellular structural changes in Fremyella diplosiphon st… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
1

Relationship

1
0

Authors

Journals

citations
Cited by 1 publication
(3 citation statements)
references
References 48 publications
0
3
0
Order By: Relevance
“…These findings are supported by a study that demonstrated visible FeO nanoparticle accumulation around the cell membrane border and increased oxidative stress in cyanobacteria [ 26 ], further substantiating the impact of iron nanoparticles on the cell membrane and the potential increase in extracellular lactate levels. In response to membrane thinning and enhanced permeability associated with ampicillin, the harmful effects of accumulated nanoparticles around the cell may be mitigated by the leakage of nZVIs into the cells [ 31 ]. Moreover, it is possible that increased intracellular iron could potentially be used as cofactors for reactions that enhance the synthesis of macromolecules such as lipids and glucose, thereby improving biofuel production efficiency and overall metabolic robustness.…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…These findings are supported by a study that demonstrated visible FeO nanoparticle accumulation around the cell membrane border and increased oxidative stress in cyanobacteria [ 26 ], further substantiating the impact of iron nanoparticles on the cell membrane and the potential increase in extracellular lactate levels. In response to membrane thinning and enhanced permeability associated with ampicillin, the harmful effects of accumulated nanoparticles around the cell may be mitigated by the leakage of nZVIs into the cells [ 31 ]. Moreover, it is possible that increased intracellular iron could potentially be used as cofactors for reactions that enhance the synthesis of macromolecules such as lipids and glucose, thereby improving biofuel production efficiency and overall metabolic robustness.…”
Section: Resultsmentioning
confidence: 99%
“…Our previous results support the findings that ampicillin and the combination regimens could result in significant changes to the cell wall of the cultures. Specifically, in B481-SD treated with 0.8 mg/L ampicillin, 3.2 mg/L nZVIs, the combination regimen and the untreated control, cell wall thinning was measured at 11.3 nm, 13 nm, 8 nm, and 14 nm, respectively [ 31 ].…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation